PREDICTORS OF MIDWIFE PERFORMANCE IN LOW BIRTH WEIGHT PREVENTION: A MULTI-FACTORIAL ANALYSIS IN RURAL NIAS, INDONESIA - Eduard Buulolo; Ermi Girsang; Sri Lestari Ramadhani Nasution; Liani Br Ginting (Pusat Studi Gender dan Anak, 2026)
Low Birth Weight (LBW) remains a significant public health issue in Indonesia, contributing to high neonatal mortality rates. This study aims to analyze the influence of tenure, supervision, compensation, and training on midwives’ performance in efforts to reduce the risk of LBW at Community Health Centers (Puskesmas) in Nias Regency. This study employed a cross-sectional design with an analytical approach. A total of 281 active midwives at Community Health Centers in Nias Regency were selected as the study sample through a questionnaire survey conducted from July to August 2025. Data were analyzed using the Chi-Square test and logistic regression to determine the most dominant factors. The results indicate that length of service, supervision, compensation, and training have a significant influence on midwives’ performance (p < 0.05). Among these four variables, compensation was identified as the most dominant factor influencing midwives’ performance in managing the risk of LBW. These findings underscore the importance of strengthening reward systems and managerial support to optimize the role of midwives on the front lines of maternal and child health care.